Graphical Based Monitoring of the Earth’s Electric Field Signal prior to the Earthquake - Astuti , Winda; Ari, F; Akmeliawati, Rini; Sediono, Wahju (2014)
Earthquake is one of the most destructive natural disasters that kill many people and des troy a lot of properties. Therefore , it is highly important to know well ahead the occurrence of earthquakes in order to reduce the number of v ictims and material losses. Earthquake prediction i s one solution to reduce such disastrous effect. The Earth’s electric field signal i s one of potential feature s that can be used for earthquake prediction generated from the released energy through a sudde n dislocation of the segment in the earth’s crust , t his signal has become one of the potential features to predict the earthquake , since it has significant changes in the amplitude of the s ignal prior to the earthquake. The significant changes of the Earth ’s electric field signals prior to the earthquake are detected and utilized i n this work. This paper present s the development of the Graphical based monitoring system for the earth’s electric field . The system uses a graphical user interface (GUI) develope d using MATLAB ®. The work is illustrated on earthquake data which occurred in Greece, between January 1, 2008 and June 30, 2008. In that period of time , thirteen earthquakes had occurred. Six of them were recorded with magnitudes greater than Ms=5R (5R), while s even of them were recorded with magnitudes greater than Ms=6R (6R)